Kuliner “Timlo Solo” sebagai Bahan Ajar BIPA dalam Upaya Internasionalisasi Bahasa Indonesia - Kristin Setyawati; Imam Nurcahyono; Khansa Hafidza; Lina Juliasari; Khundaru Saddhono (Fonologi: Jurnal Ilmuan Bahasa dan Sastra Inggris, 2024)
This article discusses the important role of teaching the Indonesian language for Foreign Speakers (BIPA) in supporting the internationalization of the language of Indonesia, with a focus on the use of the culinary material "Timlo Solo" in learning BIPA at Yale University. Through a qualitative method with a literature study approach, the study reviews the history, variation, way of making, culinary location, and role in Timlo Solo's local culinarian culture. The results of the study show that the use of Timlo solo's cooking lessons helps foreign students understand not only language, but also the cultural context, social life, and norms in Indonesia. By using culinary as a teaching material, BIPA students can gain a deeper understanding of Indonesian cultural diversity. In addition, the culinary integration in BIPA learning enriches the learning experience with practical and enjoyable aspects. In the context of the internationalization of the Indonesian language, the use of Timlo Solo’s culinary lessons at Yale University is a significant step in broadening the understanding and appreciation of Indonesia’s culture among foreign students.